A TPE composite material capable of continuously releasing negative ions and a preparation method thereof
By modifying carbon black with nitrogen doping and zinc oxide, modifying modified carbon black and treating negative ion powder with silane coupling agent, the mechanical properties and antibacterial properties of TPE materials are improved, while maintaining negative ion release properties, solving the problem of unstable mechanical properties of existing composite materials.
Patent Information
- Application Number
- CN202411064005.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-05
AI Technical Summary
When existing composite materials release negative ions, their mechanical properties are unstable, especially the addition of inorganic materials will reduce the mechanical properties of the materials.
The carbon black is treated with nitrogen and modified zinc oxide on the surface to form modified carbon black, which increases its interaction with the TPE material. In addition, the negative ion powder is refluxed in an organic solvent containing a silane coupling agent to enhance its interaction with the TPE material.
The mechanical properties and antibacterial properties of TPE materials are improved, while maintaining good negative ion release properties, solving the problem of unstable mechanical properties.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermoplastic elastomer materials, and in particular to a TPE composite material capable of sustainably releasing negative ions and a preparation method thereof. Background Art
[0002] Thermoplastic elastomer, referred to as TPE, has the elasticity of rubber at room temperature and the characteristics of plastic molding at high temperature. It is a new type of polymer material between rubber and resin, and has safety: environmentally friendly, odorless, and harmless to the human body. Based on the dual properties of rubber and plastic and the broad characteristics of TPE materials, it is widely used in the rubber industry. At the same time, it can also replace rubber in large quantities for the modification of thermoplastic resins such as polyethylene, polyvinyl chloride, and polypropylene. With the development of the automobile industry, people's requirements for automobile interiors have been significantly improved. Safe and environmentally friendly soft materials have become the development trend of automobile interior materials. TPE materials are the only choice to replace traditional automobile interior materials with their excellent processing performance, comfort performance and safety performance.
[0003] Negative ions are ions with one or more negative charges. The most common negative ions in life are negative oxygen ions. Studies have shown that negative oxygen ions have many functions such as eliminating odors, harmful gases, water treatment, and health care. Compounding substances that can release negative ions with TPE materials can improve the application scenarios of TPE materials. For example, CN117700875A discloses a TPE composite material that can release negative oxygen ions and a preparation method thereof. The composite material includes, by weight, 20 to 50 parts of styrene thermoplastic elastomer; 15 to 30 parts of thermoplastic vulcanized rubber; 10 to 30 parts of polypropylene; 5 to 15 parts of polyolefin elastomer; 1 to 10 parts of negative ion additives; 0.1 to 0.5 parts of peroxide crosslinking agents; and 1 to 2 parts of lubricants. This material has ultra-high fluidity and can release a large amount of negative oxygen ions, can effectively reduce VOC, and has high efficiency in sterilization, and can be used as a material for automotive interior decoration. However, the components of the negative ion additive are mineral powder, rare earth powder, and nano-titanium dioxide, and these inorganic components may reduce the mechanical properties of the composite material. CN117866373A discloses an antibacterial composite material for air conditioning and a preparation method thereof, wherein the composite material is prepared from 28-40wt% of TPE elastomer, 15-25wt% of magnesium silicate, 2-5wt% of tourmaline powder mixture, 0.4-0.6wt% of diamond powder, 5-8wt% of activated carbon, 5-8wt% of nano titanium dioxide particles modified with silane, 1-4wt% of polydopamine antibacterial agent, 1-5wt% of surfactant, and 30-40wt% of deionized water. This composite material has certain antibacterial properties and certain negative ion release properties. However, the preparation method of polydopamine antibacterial agent is very complicated, and the large amount of addition of inorganic materials such as magnesium silicate and titanium dioxide also cannot be ignored in terms of the mechanical properties of the composite material.
[0004] In view of the problem of unstable mechanical properties of the current TPE materials that release negative ions, it is necessary to make corresponding improvements. Summary of the invention
[0005] In order to overcome the problems existing in the prior art, the present invention provides a TPE composite material capable of continuously releasing negative ions, which comprises, by weight,
[0006] 60-90 parts of TPE elastomer, 5-15 parts of modified carbon black, 5-15 parts of modified anion powder, 1-2 parts of lubricant;
[0007] The preparation method of the modified carbon black comprises:
[0008] The carbon black is mixed with a nitrogen source and then calcined under a protective gas atmosphere to obtain nitrogen-doped carbon black;
[0009] The nitrogen-doped carbon black, soluble zinc salt, structure regulator and water are mixed and then subjected to hydrothermal reaction to obtain modified carbon black.
[0010] Carbon black can be used in TPE materials to mainly play a reinforcing role and improve tensile strength and hardness. In addition, it can also improve the wear resistance, processability and antioxidant properties of TPE materials. In order to improve the interaction between carbon black and TPE materials and make TPE materials have antibacterial properties, the present invention introduces a nitrogen source to dope carbon black with nitrogen, and generates nano zinc oxide by a hydrothermal method to form a carbon black nano zinc oxide composite material. Zinc oxide can release zinc ions, which can interfere with the metabolic process in bacterial cells and block the normal metabolism and biosynthesis process of bacteria. The doping of nitrogen in modified carbon black and the modification of zinc oxide can also enhance the antibacterial properties of the material by adding it to TPE materials.
[0011] In addition, during the calcination and doping of nitrogen-doped carbon black, the present invention uses urea, melamine, dicyandiamide and other substances as the main doping sources of nitrogen elements, and introduces imidazole-based ionic liquids with a low-temperature melting point as low-temperature accelerators, thereby enhancing the effect of the nitrogen source and carbon black during the heating process, so that the nitrogen-doped carbon black has a richer pore structure and a larger specific surface area, and does not affect the content of nitrogen elements, which makes the interaction between the nitrogen-doped carbon black and the TPE material stronger.
[0012] Furthermore, the mass ratio of the carbon black to the nitrogen source is 2 to 5:1;
[0013] The nitrogen source is prepared by mixing the main supply and the low temperature accelerator in a mass ratio of 5 to 10:1;
[0014] The main supply includes at least one of urea, melamine and dicyandiamide;
[0015] The low temperature accelerator includes at least one of 1-butyl-3-methylimidazole, 1-ethyl-3-methylimidazole, and 1-butyl-2,3-dimethylimidazole.
[0016] Furthermore, the calcination is carried out at a heating rate of 1-10°C / min to reach 400-600°C and then maintained for 1-3h.
[0017] Furthermore, the mass ratio of the nitrogen-doped carbon black, the soluble zinc salt, the structure regulator and water is 5-10:2-5:0.5-1:50-100.
[0018] Furthermore, the structure regulator includes at least one of sodium citrate, sodium gluconate and sodium benzoate.
[0019] Furthermore, after mixing the nitrogen-doped carbon black, the soluble zinc salt, the structure regulator, and water, the pH of the mixture is adjusted to 10.0-12.0;
[0020] The hydrothermal reaction is maintained at 150-200° C. for 6-12 hours.
[0021] Tourmaline and hexachlorobenzene can both permanently generate negative ions due to the presence of variable valence metals in their structures, and therefore have health-care effects. However, they are both inorganic minerals with poor compatibility with TPE materials, and it is also important to affect the mechanical properties of TPE materials while ensuring that the added amount can play a role. Therefore, the present invention also modifies them by reflux treatment in an organic solvent containing a silane coupling agent to enhance the interaction with the TPE material.
[0022] Furthermore, the preparation method of the modified negative ion powder comprises:
[0023] The negative ion powder is dispersed in an organic solvent of 3 to 5 times the mass, and then a silane coupling agent of 0.05 to 0.2 times the mass of the negative ion powder is added, and the modified negative ion powder is obtained by heating, stirring and refluxing.
[0024] Furthermore, the negative ion powder is at least one of tourmaline powder and hexacyclic stone powder;
[0025] The organic solvent is at least one of ethanol, acetone, propanol, N,N-dimethylformamide, and dimethyl sulfoxide;
[0026] In the present invention, the type of silane coupling agent is not strictly limited, and illustratively, it can be at least one of KH550, KH560, KH570, KH580, KH823, and KH832;
[0027] The temperature is raised to 60-90°C.
[0028] Furthermore, the lubricant is at least one of glyceryl monostearate, liquid paraffin, polyethylene wax, and zinc stearate.
[0029] The present invention also provides a method for preparing the above-mentioned TPE composite material capable of continuously releasing negative ions, comprising:
[0030] Putting TPE elastomer, modified carbon black, modified anion powder and lubricant into an internal mixer and mixing them to obtain a premix;
[0031] The premix is extruded to obtain a TPE composite material capable of continuously releasing negative ions.
[0032] The present invention also provides application of the above-mentioned TPE composite material capable of continuously releasing negative ions in automobile foot pads.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention performs nitrogen doping on carbon black and then modifies the surface with zinc oxide to obtain modified carbon black. The modified carbon black has a stronger interaction with the TPE material, which improves the mechanical properties of the TPE material to a certain extent. The introduction of zinc oxide also gives the TPE material good antibacterial properties. At the same time, the negative ion powder is refluxed in an organic solvent containing a silane coupling agent to obtain the modified negative ion powder, which improves the interaction between the negative ion powder and the TPE material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The scanning electron microscope images of the carbon black used in Example 1 of the present invention and the modified carbon black prepared in Example 1 are shown. DETAILED DESCRIPTION
[0036] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0037] Introduction of some raw materials used in the examples and comparative examples of the present invention:
[0038] TPE elastomer, product number EPK, purchased from Kunshan Kexin Polymer Materials Co., Ltd.;
[0039] Carbon black, product number N660, was purchased from Shandong Wanhua Tianhe New Materials Co., Ltd.;
[0040] Glyceryl monostearate, product number 526, was purchased from Hebei Kelongduo Biotechnology Co., Ltd.;
[0041] Tourmaline powder, item number dqs, mesh number 3000, was purchased from Shijiazhuang Huabang Mineral Products Co., Ltd.
[0042] 1-Butyl-3-methylimidazole, 1-ethyl-3-methylimidazole, and 1-butyl-2,3-dimethylimidazole were purchased from Wuhan Belle Biopharmaceutical Technology Co., Ltd. Other raw materials not mentioned are common raw materials. The above content is only to help illustrate the present invention and shall not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase or prepare the same / similar raw materials from the market. These contents will not be repeated in the examples.
[0043] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] A method for preparing a TPE composite material capable of continuously releasing negative ions, comprising the following steps:
[0046] S1, weigh 8kg TPE elastomer, 1kg modified carbon black, 1kg modified anion powder, 0.1kg glyceryl monostearate;
[0047] S2, putting TPE elastomer, modified carbon black, modified anion powder and glyceryl monostearate into an internal mixer, heating to 220° C., and mixing at a speed of 20 rpm for 10 min to obtain a premix;
[0048] S3. Extruding the obtained premix to obtain a TPE composite material capable of continuously releasing negative ions.
[0049] Wherein, the preparation method of modified carbon black is:
[0050] T1. 1 kg of carbon black, 0.27 kg of urea and 0.03 kg of 1-butyl-3-methylimidazole were mixed and transferred to a muffle furnace in a nitrogen atmosphere. The temperature was raised to 550°C at a heating rate of 3°C / min and then kept at this temperature for 2 hours. The heating was then stopped. After natural cooling, the black powder was collected, washed three times with ethanol and water respectively, and dried in a constant temperature oven at 80°C for 12 hours to obtain nitrogen-doped carbon black.
[0051] T2. Mix 1 kg of nitrogen-doped carbon black, 0.5 kg of zinc acetate dihydrate, 0.05 kg of sodium benzoate and 8 kg of water, stir at 300 rpm for 15 min, adjust the pH to 11.5 with sodium hydroxide, transfer to a reactor and place in a constant temperature oven at 160°C for hydrothermal reaction for 8 h. After natural cooling, filter and collect insoluble matter, wash with ethanol and water three times each, and dry in a constant temperature oven at 120°C for 8 h to obtain modified carbon black.
[0052] The preparation method of the modified negative ion powder is as follows: 1 kg of tourmaline powder and 4 kg of ethanol are mixed and stirred at a speed of 300 rpm for 30 minutes, then 0.1 kg of silane coupling agent KH550 is added, and the temperature is raised to 80° C. and stirred and refluxed for 5 hours, and then the insoluble matter is filtered and collected and dried in a constant temperature oven at 80° C. for 12 hours to obtain the modified negative ion powder.
[0053] Example 2
[0054] The difference compared with Example 1 is that in step T1 of the method for preparing modified carbon black, the masses of urea and 1-butyl-3-methylimidazole are 0.25 kg and 0.05 kg respectively.
[0055] Example 3
[0056] The difference compared with Example 1 is that in step T1 of the method for preparing modified carbon black, melamine is used instead of urea.
[0057] Example 4
[0058] The difference compared with Example 1 is that in step T1 of the method for preparing modified carbon black, dicyandiamide is used instead of urea.
[0059] Example 5
[0060] The difference compared with Example 1 is that in step T1 of the method for preparing modified carbon black, 1-ethyl-3-methylimidazole is used instead of 1-butyl-3-methylimidazole.
[0061] Example 6
[0062] The difference compared with Example 1 is that in step T1 of the method for preparing modified carbon black, 1-butyl-2,3-dimethylimidazole is used instead of 1-butyl-3-methylimidazole.
[0063] Comparative Example 1
[0064] The difference compared with Example 1 is that in step T1 of the method for preparing modified carbon black, the masses of urea and 1-butyl-3-methylimidazole are 0.2 kg and 0.1 kg respectively.
[0065] Comparative Example 2
[0066] The difference compared with Example 1 is that: the preparation method of modified carbon black is as follows: 1 kg of carbon black, 0.5 kg of zinc acetate dihydrate, 0.05 kg of sodium benzoate, and 8 kg of water are mixed, and then stirred at a speed of 300 rpm for 15 minutes, and the pH is adjusted to 11.5 with sodium hydroxide, and then transferred to a reactor and placed in a constant temperature oven at 160°C for hydrothermal reaction for 8 hours. After natural cooling, the insoluble matter is collected by filtration, washed three times with ethanol and water respectively, and then dried in a constant temperature oven at 120°C for 8 hours to obtain modified carbon black.
[0067] Comparative Example 3
[0068] A method for preparing a TPE composite material capable of continuously releasing negative ions, which differs from Example 1 in that sodium benzoate is not added in step T2 of the method for preparing modified carbon black.
[0069] Comparative Example 4
[0070] A method for preparing a TPE composite material capable of continuously releasing negative ions, comprising the following steps:
[0071] S1, weigh 8kg TPE elastomer, 1kg modified carbon black, 1kg tourmaline powder, 0.1kg glyceryl monostearate;
[0072] S2, putting TPE elastomer, modified carbon black, tourmaline powder and glyceryl monostearate into an internal mixer, heating to 220° C., and mixing at a speed of 20 rpm for 10 min to obtain a premix;
[0073] S3. Extruding the obtained premix to obtain a TPE composite material capable of continuously releasing negative ions.
[0074] Wherein, the preparation method of modified carbon black is the same as that in Example 1.
[0075] Comparative Example 5
[0076] A method for preparing a TPE composite material capable of continuously releasing negative ions, comprising the following steps:
[0077] S1, weigh 8kg TPE elastomer, 1kg nitrogen-doped carbon black, 1kg modified anion powder, and 0.1kg glyceryl monostearate;
[0078] S2, putting TPE elastomer, nitrogen-doped carbon black, modified anion powder and glyceryl monostearate into an internal mixer, heating to 220° C., and mixing at a speed of 20 rpm for 10 min to obtain a premix;
[0079] S3. Extruding the obtained premix to obtain a TPE composite material capable of continuously releasing negative ions.
[0080] Wherein, the preparation method of modified negative ion powder is the same as that of Example 1;
[0081] The preparation method of nitrogen-doped carbon black is as follows: 1 kg of carbon black, 0.27 kg of urea, and 0.03 kg of 1-butyl-3-methylimidazole are mixed and transferred to a muffle furnace in a nitrogen atmosphere, and the mixture is heated to 550°C at a heating rate of 3°C / min and then kept warm for 2 hours. The heating is then stopped, and the black powder is collected after natural cooling. The black powder is washed three times with ethanol and water respectively, and then dried in a constant temperature oven at 80°C for 12 hours to obtain nitrogen-doped carbon black.
[0082] Test Case
[0083] The microscopic morphologies of the raw carbon black used in the example and the modified carbon black prepared in Example 1 were observed using a scanning electron microscope. Figure 1 shown.
[0084] The nitrogen isothermal adsorption-desorption curves of the modified carbon black in the embodiments and comparative examples were tested to obtain the specific surface area and pore size. The nitrogen content of the modified carbon black in the embodiments and comparative examples was also tested. The results are shown in Table 1.
[0085] Table 1 Specific surface area and pore size of modified carbon black
[0086] <![CDATA[Specific surface area (m 2 / g)]]> Nitrogen content (%) Example 1 265.3 0.14 Example 2 228.8 0.09 Example 3 232.7 0.11 Example 4 246.1 0.12 Example 5 245.7 0.12 Example 6 232.8 0.11 Comparative Example 1 185.3 0.07 Comparative Example 2 125.4 - Comparative Example 3 225.3 0.11 Carbon Black 156.1 -
[0087] From the test results in Table 1, it can be seen that compared with carbon black, Examples 1 to 6, Comparative Example 1, and Comparative Example 3 increase the specific surface area after adding a nitrogen source for calcination. The specific surface area of Comparative Example 2, which directly prepares zinc oxide on carbon black without nitrogen doping, decreases relative to carbon black. This is because zinc oxide blocks the pore size of carbon black. Examples 1 to 2 and Comparative Example 1 illustrate that the ratio of urea and 1-butyl-3-methylimidazole has a greater effect on the specific surface area of modified carbon black. This may be because when the proportion of 1-butyl-3-methylimidazole is too large, the etching of carbon black is enhanced, the pore structure collapses, and the specific surface area is reduced. Compared with Comparative Example 3, Example 1 illustrates that the addition of sodium benzoate may improve the distribution of zinc oxide in nitrogen-doped carbon black, inhibit zinc oxide agglomeration and pore blockage. The nitrogen element test results show that the increase in the proportion of ionic liquids will promote the decomposition of nitrogen sources and thus reduce the nitrogen content.
[0088] The tensile mechanical properties of TPE composites were tested with reference to the standard GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics". The results are shown in Table 2.
[0089] Table 2 Tensile mechanical properties of TPE composites
[0090] Tensile strength (MPa) Example 1 11.8 Example 2 11.2 Comparative Example 1 10.7 Comparative Example 2 8.3 Comparative Example 3 9.6 Comparative Example 4 6.7 Comparative Example 5 10.5
[0091] From the test results in Table 2, it can be seen that the tensile strength of Comparative Example 4 is the lowest, which is caused by the poor compatibility of unmodified tourmaline with TPE materials. The tensile strengths of Example 1, Example 2, and Comparative Example 1 decrease in turn, which corresponds to the specific surface area. The modified carbon black with a larger specific surface area has a stronger effect on the TPE material. Example 1 and Comparative Example 5 have greater tensile strengths, which shows that the introduction of zinc oxide further enhances the effect of the modified carbon black with the TPE material and further improves the strength.
[0092] The antibacterial properties of TPE composite materials were tested with reference to the standard GB / T 31402-2023 “Determination of antibacterial activity on the surfaces of plastics and other non-porous materials”, and the results are shown in Table 3.
[0093] Table 3 Antibacterial properties of TPE composites
[0094] 6h antibacterial rate of Escherichia coli (%) Example 1 99.9 Example 2 99.9 Comparative Example 1 99.9 Comparative Example 2 84.6 Comparative Example 3 93.2 Comparative Example 4 99.9 Comparative Example 5 64.3
[0095] The antibacterial rates of Comparative Examples 2, 3 and 5 are relatively poor, which indicates that nitrogen doping of carbon black, introduction of zinc oxide, and regulation of zinc oxide are particularly important for the antibacterial properties of TPE composite materials.
[0096] The negative oxygen ion release of the TPE composite material was also tested using a negative oxygen ion detector, and the results are shown in Table 4.
[0097] Table 4 Negative oxygen ion release of TPE composite materials
[0098] <![CDATA[Negative oxygen ion release amount in 10s (pcs / cm 3 ).]]> Example 1 5432 Example 2 5199 Comparative Example 1 5078 Comparative Example 2 3672 Comparative Example 3 4429 Comparative Example 4 5679 Comparative Example 5 4678
[0099] The negative oxygen ion release of Example 1 and Comparative Example 4 is similar, which shows that the modification of tourmaline does not substantially affect the negative ion release performance. The release performance of Example 1 is significantly improved compared to Comparative Examples 2 and 5, which shows that nitrogen doping in carbon black and the introduction of zinc oxide also contribute to the release of negative ions.
[0100] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A TPE composite material capable of continuously releasing negative ions, characterized in that: In parts by mass, it includes: 60-90 parts of TPE elastomer, 5-15 parts of modified carbon black, 5-15 parts of modified anion powder, 1-2 parts of lubricant; The preparation method of the modified carbon black comprises: The carbon black is mixed with a nitrogen source and then calcined under a protective gas atmosphere to obtain nitrogen-doped carbon black; The nitrogen-doped carbon black, soluble zinc salt, structure regulator and water are mixed and then subjected to hydrothermal reaction to obtain modified carbon black. The mass ratio of the nitrogen-doped carbon black, the soluble zinc salt, the structure regulator, and water is 5-10:2-5:0.5-1:50-100; The structure adjusting agent includes at least one of sodium citrate, sodium gluconate and sodium benzoate; The mass ratio of the carbon black to the nitrogen source is 2-5:1; The nitrogen source is prepared by mixing the main supply and the low temperature accelerator in a mass ratio of 5 to 10:1; The main supply includes at least one of urea, melamine and dicyandiamide; The low temperature accelerator includes at least one of 1-butyl-3-methylimidazole, 1-ethyl-3-methylimidazole, and 1-butyl-2,3-dimethylimidazole; The preparation method of the modified negative ion powder comprises: The negative ion powder is dispersed in an organic solvent of 3 to 5 times the mass, and then a silane coupling agent of 0.05 to 0.2 times the mass of the negative ion powder is added, and the modified negative ion powder is obtained by heating, stirring and refluxing.
2. The TPE composite material capable of sustainably releasing negative ions according to claim 1, characterized in that: The calcination is carried out at a heating rate of 1-10°C / min to a temperature of 400-600°C and then maintained for 1-3h.
3. The TPE composite material capable of sustainably releasing negative ions according to claim 1, characterized in that: After mixing nitrogen-doped carbon black, soluble zinc salt, structure regulator and water, the pH of the mixture is adjusted to 10.0-12.0; The hydrothermal reaction is maintained at 150-200° C. for 6-12 hours.
4. The TPE composite material capable of sustainably releasing negative ions according to claim 1, characterized in that: The negative ion powder is at least one of tourmaline powder and hexacyclic stone powder; The organic solvent is at least one of ethanol, acetone, propanol, N,N-dimethylformamide, and dimethyl sulfoxide; The temperature is raised to 60-90°C.
5. The TPE composite material capable of sustainably releasing negative ions according to claim 1, characterized in that: The lubricant is at least one of glyceryl monostearate, liquid paraffin, polyethylene wax and zinc stearate.
6. A method for preparing a TPE composite material capable of sustainably releasing negative ions as claimed in any one of claims 1 to 5, characterized in that: include, Putting TPE elastomer, modified carbon black, modified anion powder and lubricant into an internal mixer and mixing them to obtain a premix; The premix is extruded to obtain a TPE composite material capable of continuously releasing negative ions.
7. Application of the TPE composite material capable of sustainably releasing negative ions as claimed in any one of claims 1 to 5 in automobile foot mats.
Citation Information
Patent Citations
Antibacterial composite material for air conditioner and preparation method of antibacterial composite material
CN117866373A
Functional protection tool material used in sports field and preparation method of functional protection tool material
CN107057140A
Minor-cycle water inlet pipe for engine and preparation method thereof
CN111171406A